El clima organizacional y la satisfacción laboral enla Empresa Pública de Movilidad de la Mancomunidad de Cotopaxi (EPMC). - Alvarado Mendoza, Carlos Michael (2023)
The research project analyzes the relationship between the organizational climate and job satisfaction, which are the perceptions that employees have regarding their work, It focused on the analysis of the relationship between the organizational climate and job satisfaction in the Public Mobility Company of the Commonwealth of Cotopaxi (EPMC). The methodology used has a quantitative approach and a descriptive correlational methodology, field modality, and cross-sectional type. Two instruments were used for the diagnosis: to measure the organizational climate (OC), the questionnaire proposed by Araujo et al. (2011), and to measure job satisfaction (SL) the one proposed by Sotomayor, F. (2013). It was applied to the 73 collaborators of the institution. As a result, it was obtained that the organizational climate has a positive index with an average of 4 out of 5, which means that most of the officials agree with the management style, recognition, autonomy, enthusiasm and support, rewards, and innovation that exists within the institution. The satisfaction index averaged 4 out of 5, which indicates that employees are satisfied with their relationship with their superiors, physical conditions, participation in decision-making, recognition, and with their work in general. The data was analyzed through the SPSS to obtain the Spearman coefficient, yielding a result of 0.603, which means that there is a moderate relationship between the organizational climate and job satisfaction within the EPMC.